2000
DOI: 10.1080/016502500383494
|View full text |Cite
|
Sign up to set email alerts
|

Peer acceptance in early childhood and subtypes of socially withdrawn behaviour in China, Russia, and the United States

Abstract: a To assess whether subtypes of withdrawal could be similarly identi ed by teachers and linked to peer group adjustment in mainland China, Russia, and the United States, 642 4-to 6-year-old children in these diverse cultural contexts were rated on items re ecting reticent, solitary-passive, solitary-active, and sociable behaviour (cf. Coplan & Rubin, 1998). Linkages of childhood withdrawal to peer group adjustment were also investigated using peer sociometric ratings. Findings, based on multisample con rmatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
166
6
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(192 citation statements)
references
References 53 publications
15
166
6
5
Order By: Relevance
“…This research identified (a) conflicted shyness, defined by social fear and anxiety despite a desire to interact socially and reflected in reticent behavior and (b) social disinterest, defined by lack of a strong motivation to engage in social interaction. Indeed, this and other research suggests that both types are associated with difficulties in emotion regulation, interactive peer play and peer acceptance (Coplan et al, 2004;Hart et al, 2000).…”
Section: Emotion Regulationmentioning
confidence: 64%
“…This research identified (a) conflicted shyness, defined by social fear and anxiety despite a desire to interact socially and reflected in reticent behavior and (b) social disinterest, defined by lack of a strong motivation to engage in social interaction. Indeed, this and other research suggests that both types are associated with difficulties in emotion regulation, interactive peer play and peer acceptance (Coplan et al, 2004;Hart et al, 2000).…”
Section: Emotion Regulationmentioning
confidence: 64%
“…It is important to note that shyness and social withdrawal become increasingly salient and negative to peers with age. In early childhood, shy and socially withdrawn children do not appear to be rejected by their classmates (Hart et al, 2000;Ladd & Burgess, 1999); however, by mid-to-late childhood and early adolescence, many shy, socially withdrawn children do become rejected by their peers (Boivin, Hymel, & Bukowski, 1995;Rubin, Chen, & Hymel, 1993). Moreover, shy/ withdrawn children are also often the targets of peer victimization (Hanish & Guerra, 2004;Hodges, Malone, & Perry, 1997;Olweus, 1993).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Russia has traditionally been classified as a collectivist country (Realo & Allik, 1999;Triandis, 1995) but, given patterns of political and social change in the last few decades, it is now more accurately placed in an intermediate stage on Hofstede's standard dimension of collectivism -individualism scale (Hart et al, 2000;Naumov & Puffer, 2000). Current social norms and economic patterns may require youth to display more individual initiative and greater competitiveness in social groups.…”
Section: Social and Cultural Changesmentioning
confidence: 99%